In vivo and in vitro study on the combination extract of Curcuma zedoaria and Astragalus membranaceus as an adjuvant for PRRSV inactivated vaccine and its preliminary application in piglets - Tu, Teng; Zhang, Guidong; Du, Chengchao; Luo, Yan; Yao, Xueping; Yang, Zexiao; Ren, Meishen; Wang, Yin; Jiang, Dike (Frontiers in Microbiology, 2024)
BackgroundPorcine Reproductive and Respiratory Syndrome Virus (PRRSV) is a single-stranded positive-sense RNA virus that severely impacts the global swine industry. Recently, variation and recombination of this pathogen have led to more recombinant strains. However, commercial PRRSV vaccines provide limited protection, and no effective therapeutic drugs are available in clinical settings. Astragalus membranaceus (AM) has anti-inflammatory and immune-enhancing properties, while Curcuma zedoaria (CZ) possesses anti-inflammatory, antibacterial, and antitumor effects. The combination of AM and CZ, originating from the “Lichong Tang” recorded in the “Intergrating Chinese and Western Medicine” offers complementary and synergistic benefits.MethodsIn this study, the AM extract, CZ extract, and various ratios of CZ-AM extracts were prepared using the decoction method. The NADC30-like PRRSV strain SCCD22 was used for viral challenge. The optimal ratio and mode of action of the CZ-AM extract on Pams-163 were assessed by measuring viral copies and mRNA expression of cytokines. Subsequently, the optimal ratio of combined extracts identified in vitro was used as an adjuvant for the PRRSV inactivated vaccine in 28-day-old piglets. Clinical symptom observations, peripheral blood lymphocyte proliferation assays, levels of PRRSV antibody, cytokine secretion, and NLRP3 inflammasome mRNA were conducted to evaluate the potential of the CZ-AM extract as an adjuvant for the PRRSV inactivated vaccine.ResultsResults showed that the CZ-AM extract inhibited PRRSV in vitro, with the best ratio of CZ to AM being 1:4. Animal experiments demonstrated that using the CZ-AM extract as an adjuvant for the PRRSV inactivated vaccine significantly increased the body weight of piglets, elevated serum PRRSV antibody levels, and enhanced the piglets’ inflammatory response. mRNA analysis indicated that the CZ-AM extract inhibited key inflammatory pathways (TLR4/NLRP3/IL-1β), reducing the expression of inflammatory factors. Lymphocyte proliferation assays indicated that the CZ-AM extract significantly stimulated T and B lymphocyte proliferation.ConclusionThis study not only deepens the understanding of the pharmacological effects of AM and CZ but also expands the application of traditional Chinese medicine in the prevention and control of animal diseases. Furthermore, it provides new insights and methods for optimizing PRRSV vaccines, offering significant scientific value and broad application prospects.